Pengaruh Profitabilitas Terhadap Return Saham Dengan Nilai Perusahaan Sebagai Variabel Mediasi Pada Indeks Saham Syariah Indonesia Sektor Industri Barang Konsumsi Periode 2013-2017 - Destiana Kumala (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Raden Fatah Palembang, Indonesia, 2020)
Abstract This study aims to examine the effect of profitability on stock returns with firm value as the mediating variable. The population in this study are manufacturing companies in the consumer goods industry sector which are listed on the Indonesian Sharia Shock Index (ISSI), the independent variable in this study is profitabilty (X), proxied by using return on equity, the dependent variable stock returns (Y). As measured by the calculation of the stock return formula and the mediating variable, namely the firm value (Z) is proxied by the price to book value (PBV). This research method uses quantitative research methods using secondary data. Samples were taken based on predetermined criteria. From the sampling method applied, it was obtained 13 manufacturing companies in the consumer goods industry sector that were listed on the Indonesia Sharia Stock Index (ISSI) 2013 – 2017 with data analysis using the SPSS 22 program. The results showed that profitability had an effect on firm value, profitability had no effect on stock return, firm value had an effect on stock returns, profitability had an effect on stock returns mediated by firm value. keywords : profitability,stock return, firm value